2023
DOI: 10.3389/fmicb.2022.951130
|View full text |Cite
|
Sign up to set email alerts
|

The power of the smallest: The inhibitory activity of microbial volatile organic compounds against phytopathogens

Abstract: Plant diseases caused by phytopathogens result in huge economic losses in agriculture. In addition, the use of chemical products to control such diseases causes many problems to the environment and to human health. However, some bacteria and fungi have a mutualistic relationship with plants in nature, mainly exchanging nutrients and protection. Thus, exploring those beneficial microorganisms has been an interesting and promising alternative for mitigating the use of agrochemicals and, consequently, achieving a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 224 publications
0
18
0
Order By: Relevance
“…Plant growth parameters are frequently reduced in response to salt stress conditions [ 53 ]. However, some studies have reported that mVOCs can induce tolerance against abiotic stress [ 25 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Plant growth parameters are frequently reduced in response to salt stress conditions [ 53 ]. However, some studies have reported that mVOCs can induce tolerance against abiotic stress [ 25 , 54 , 55 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are many reports where PGPR VOC blends have shown antifungal properties against a wide range of phytopathogenic fungi [ 70 ], although the mechanisms involved in such processes remain poorly understood. Recent studies have suggested that VOCs affect phytopathogens by modulating the activity of specific enzymes and altering motility and protein production, which subsequently influence growth, cell morphology and virulence factors [ 53 ]. VOCs from Pseudomonas sp.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to non-volatile natural products, volatile organic compounds (VOCs) are increasingly recognized as promising bioactive molecules due to their wide range of ecological functions [13]. Biological VOCs are produced by plants [14], fungi [15], and bacteria [16]. Microbial VOCs have been reported to be by-products produced by microorganisms during primary metabolism or secondary metabolism [17].…”
Section: Introductionmentioning
confidence: 99%